Implementation of Islamic Religious Local Content Policy at SMP Negeri 2 Kabuh Jombang - Moch Sya'roni Hasan; Mar'atul Azizah; Solechan Solechan (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to describe and find a model for the application of Islamic Religious Local Content in SMP Negeri 2 Kabuh Jombang. The problems that will be studied in this research are: How to prepare, implement, and evaluate Islamic Religious Local Content in SMP (Junior High School) Negeri 2 Kabuh Jomban. This research is field research and the approach used is a qualitative approach with a case study type. Data collection techniques using interview techniques, observation, and documentation. The data analysis technique uses data collection, data condensation, data presentation, and concluding. The result of the research is that the application of Islamic religious local content is prepared in the form of a concept for making classroom devices by adjusting the Islamic religious local content curriculum, implementation using demonstration and drill methods. Evaluation using written test and practice of Islamic religious skills. The results of this study are expected to contribute to solving PAI (Pendidikan Agama Islam) learning problems that have been occurring mainly in public schools. For example, the lack of class hours so that PAI material cannot be delivered optimally. Suggestions for future researchers, maybe the impact of implementing local Islamic religious content can be further deepened, both at school and in the family environment.